Perubahan Cara Pandang Wanita Jepang Terhadap Perkawinan dan Kaitannya dengan Shoushika - Linda Unsriana (Bina Nusantara University, 2014)
Declining of the birth rate (shoushika) in Japan is quite significant nowadays. If this problem persists, it is estimated in 2060 Japan will have zero birth rate. Some various studies have been carried out to find solution to this problem. This paper studies on declining of birth rate from Japanese women perspective in terms of marriage. In a survey in 1972, one of the question to the respondents said whether they want to marry, about 80% of men and women answering they want to get married. But this view changed – which in 1990 they were asked the same question, the answer to get married down by half. This new perspective as well as shoushika is interesting to be studied further. This is a literature study paper by reviewing books, journal articles, and also some statistic data to be analyzed and concluded.